2018
DOI: 10.1007/s10916-018-1072-9
|View full text |Cite
|
Sign up to set email alerts
|

Generative Adversarial Network for Medical Images (MI-GAN)

Abstract: Deep learning algorithms produces state-of-the-art results for different machine learning and computer vision tasks. To perform well on a given task, these algorithms require large dataset for training. However, deep learning algorithms lack generalization and suffer from over-fitting whenever trained on small dataset, especially when one is dealing with medical images. For supervised image analysis in medical imaging, having image data along with their corresponding annotated ground-truths is costly as well a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 200 publications
(107 citation statements)
references
References 34 publications
0
104
0
3
Order By: Relevance
“…Most works on the GANs have reported the use of an encoder-decoder style structure for generator network. So, a similar architecture for the generator is retained [37] [43]. This allows us to use noise code in a natural manner.…”
Section: B Generator Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Most works on the GANs have reported the use of an encoder-decoder style structure for generator network. So, a similar architecture for the generator is retained [37] [43]. This allows us to use noise code in a natural manner.…”
Section: B Generator Architecturementioning
confidence: 99%
“…They achieved competitive dice score on DRIVE and STARE datasets of retinal fundoscopic images [36]. In MI-GAN [37], the authors proposed a framework for the generation of synthetic medical images as well as their segmented masks. The synthetic images and their masks are further used for training of segmentation network, and the authors reported state-ofthe-art dice score on DRIVE and STARE datasets [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning [13]- [15] has greatly revolutionized many different domains involving analysis of a large image, audio, text, video, or tabular data. Of particular relevance to the work reported in this paper are the advancement made in image and video processing using deep learning methods for segmentation, identification, recognition [16], deep learning for time-series data (e.g., speech) [17], and deep learning in medical imaging [12], [18]. Hence, we present the relevant details on deep learning for segmentation and signal detection in the subsequent text.…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning (a sub branch of machine learning) algorithms have been popular for automatic recognition of digits and characters of different languages. Deep networks can be trained in supervised fashion requiring labels, or in an unsupervised way without requirements of labels [3], [4], [5]. In this work, we use an autoencoder network and a convolutional neural network (CNN) trained with 85% portion of the dataset and tested with the remaining 15% of the data.…”
Section: Introductionmentioning
confidence: 99%